A warrior and a killer or a pacifist? On the relationship of human nature, aggression and violence, as well as war and human social life - Zbigniew Paweł Małysz (Rozprawy Społeczne)
Abstract This paper is an original attempt to describe the relationship between human nature, aggression and violence, as well as war and human social life in the context (polish edition) of David Livingstone Smith's (2011b) monograph: The most dangerous of animals. Human nature and the causes of Wars (originally published in 2007). Its aim is to familiarize the reader with the title analytical problem, with particular emphasis on the perspective of psychology (individualism) and sociology (collectivism) as well as (partially) social anthropology based on the original analysis of existing data (as a consequence of which the analytical-synthetic method was used). As a result of the analyzes, the author presents an attempt to answer the title question: Is man - by nature - a warrior and a killer, or is he a pacifist?